George W. Bush and Barack Obama’s Policies Towards the ‘New Middle East’: Promoting Democracy or Destroying Social Peace? - بغياني, اميرة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
The strategy that came to be largely associated with the invasion of Iraq, by overthrowing Saddam’s regime would precipitate domino democratization throughout the Middle East, has been plagued into a disaster of destruction. This article aims to analyze Bush’s policy with regard to state-building efforts in the region, and the extent to which his administration is committed itself to promote democracy or destroy social peace of the Arab nations. The study also brings into focus Obama’s policy to a set of challenges following the emergence of ISIS and the Arab uprisings. It is concluded that Bush’s neoconservative government and Obama’s administration have failed at promoting democracy in the Middle East.